Subject Positions and Information-Structural Diversification in the History of English - Theresa Bibenauer (Universitat Autònoma de Barcelona, 2011)
The aim of this paper is to integrate Information Structure/IS-related insights of past work on the subject system of Old English with a particular formal account of word-order variation and change in earlier English that did not take IS considerations into account. We offer a first detailed formal account of how the IS-sensitive Old English subject positions can be understood in the context of an OV system which was becoming increasingly VO, and thereafter outline subject-related developments during Middle English and Early Modern English, leading us to the present day. Against the background of these diachronic developments, our contention is that English has, in one way or another, exhibited IS-sensitive subject positions throughout its history and that, as argued by Kiss (1996), it continues to do so today.